Pengaruh Customer Experience dan E-Service Quality terhadap Loyalitas Pelanggan melalui Customer Satisfaction pada Pengguna Aplikasi Dana. - Simatupang, Amrin Januarson; Lestari, Indawati (Mahesa Research Center, 2025)
This study analyzes the effect of customer experience and e-service quality on customer loyalty through customer satisfaction for DANA application users in Medan Selayang District. With the increasing use of digital wallets, customer satisfaction is a major factor in building loyalty. This research uses a quantitative approach with a survey method. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that customer experience and e-service quality have a positive effect on customer satisfaction, which in turn increases customer loyalty. The findings confirm that user experience and e-service quality play an important role in retaining customers. The implications of this research can be a reference for digital wallet service providers, especially DANA, in improving user experience strategies and service optimization to increase customer loyalty.